Logging Road, Transportation and Outward Migration in Sarawak: The Local Perspective of Marudi Town - Wong, Bemen Win Keong (Universiti Teknologi Mara Cawangan Kedah, 2013)
Marudi Town, the major town of Marudi District, was called an isolated town by the local folks as there was no road connecting it to the nearest city, Miri. Since 2005, a logging road was made accessible to the local to commute between Marudi Town and Miri City. The State Government once believed that roads stimulate outward migration. That was why; there is no active plan to build a road between Marudi Town and Miri City for the purpose of halting outward migration (Roads in Marudi, 2007). This paper examines what really perceive by the local people in Marudi Town on the logging road, the impact of the road on transportation, views on outward migration and the future migration plan of the local people.